Surface Morphology of 6-Inch SiC Single Crystals in Solution Growth on Si-Face, C-Face and (<semantics>10<mover accent="true">1¯</mover><mover accent="true">2¯</mover></semantics>) Plane - Gangqiang Liang; Jiayi Kuang; Yilin Su; Yuan Liu (Crystals)
For solution growth of 6-inch 4H-SiC bulk crystals, the surface step morphology of the crystals grown on Si-face, C-face and (<semantics>10<mover accent="true">1¯</mover><mover accent="true">2¯</mover></semantics>) plane was systematically characterized by laser confocal microscopy. The 2D-nucleation and step-bunching were likely to occur during the 30 h growth on Si-face, leading to a rough surface with a macro-step height over 60 μm. By contrast, the step heights were maintained at 0.1–1 μm during 60 h growth on C-face, exhibiting good morphological stability for long-term growth. Moreover, the SiC crystal grown on the (<semantics>10<mover accent="true">1¯</mover><mover accent="true">2¯</mover></semantics>) plane illustrated its excellence in producing fine steps, which is attributed to the smaller interfacial energy between the solution and (<semantics>10<mover accent="true">1¯</mover><mover accent="true">2¯</mover></semantics>) substrates, suggesting that it offers a better approach to growing SiC single bulk crystals.